2020
DOI: 10.1007/s00405-020-06233-y
|View full text |Cite
|
Sign up to set email alerts
|

Individual variability of olfactory fMRI in normosmia and olfactory dysfunction

Abstract: Purpose The diagnosis of olfactory dysfunction is mainly based on psychophysical measurements. The aim of the current study was to investigate how well the olfactory functional magnetic resonance imaging (fMRI) can effectively distinguish between normosmic people and subjects with olfactory dysfunction. Methods Thirty-eight participants were recruited for the study. Group 1 consisted of 22 subjects with olfactory dysfunction (mean age = 44.3 years,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 29 publications
0
19
0
Order By: Relevance
“…1202 Another study investigated patients with idiopathic olfactory loss, considered as at risk for developing PD, in comparison to patients with PD and normosmic controls. 1203 This study found that, on a group level, fractional anisotropy measured at the level of the substantia nigra was decreased in idiopathic patients and patients with PD in comparison to controls. This finding suggests a reduced integrity of the substantia nigra in patients with idiopathic smell loss, supporting their PD at-risk status.…”
mentioning
confidence: 68%
See 3 more Smart Citations
“…1202 Another study investigated patients with idiopathic olfactory loss, considered as at risk for developing PD, in comparison to patients with PD and normosmic controls. 1203 This study found that, on a group level, fractional anisotropy measured at the level of the substantia nigra was decreased in idiopathic patients and patients with PD in comparison to controls. This finding suggests a reduced integrity of the substantia nigra in patients with idiopathic smell loss, supporting their PD at-risk status.…”
mentioning
confidence: 68%
“…One study investigated patients with congenital anosmia and found that these patients have network dysfunction but intact structural integrity 1202 . Another study investigated patients with idiopathic olfactory loss, considered as at risk for developing PD, in comparison to patients with PD and normosmic controls 1203 . This study found that, on a group level, fractional anisotropy measured at the level of the substantia nigra was decreased in idiopathic patients and patients with PD in comparison to controls.…”
Section: Evaluation and Diagnosismentioning
confidence: 99%
See 2 more Smart Citations
“…This method offers the possibility to study the processing of olfactory information and constitutes an objective assessment of olfactory functioning. Although fMRI has significantly increased our knowledge of human olfactory processing, its clinical value on an individual level remains somewhat debatable [ 1 ••].…”
Section: Introductionmentioning
confidence: 99%